2019
DOI: 10.15252/emmm.201809539
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the selective estrogen receptor modulator bazedoxifene to suppress gastrointestinal cancer growth

Abstract: Excessive signaling through gp130, the shared receptor for the interleukin ( IL )6 family of cytokines, is a common hallmark in solid malignancies and promotes their progression. Here, we established the in vivo utility of bazedoxifene, a steroid analog clinically approved for the treatment of osteoporosis, to suppress gp130‐dependent tumor growth of the gastrointestinal epithelium. Bazedoxifene administration reduced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 51 publications
(104 reference statements)
2
33
0
Order By: Relevance
“…Bazedoxifene and raloxifene exhibit anti-inflammatory activity in arthritis (5) and due to their anti-IL6 signaling activity were also found to have anticancer effects, directly associated to their verified potential to inhibit IL6 signaling in animals, at doses similar to therapeutic doses in humans (6). Bazedoxifene and raloxifene may therefore represent cheaper and easier alternatives for large scale production, compared to humanized IL6 signaling antibodies for the treatment of severe COVID-19-related lung complications.…”
mentioning
confidence: 99%
“…Bazedoxifene and raloxifene exhibit anti-inflammatory activity in arthritis (5) and due to their anti-IL6 signaling activity were also found to have anticancer effects, directly associated to their verified potential to inhibit IL6 signaling in animals, at doses similar to therapeutic doses in humans (6). Bazedoxifene and raloxifene may therefore represent cheaper and easier alternatives for large scale production, compared to humanized IL6 signaling antibodies for the treatment of severe COVID-19-related lung complications.…”
mentioning
confidence: 99%
“…In adult intestines, CDX2 controls the balance between proliferation and differentiation, and its depletion results in dedifferentiation, leading to cancer pathogenesis 43 , 44 . In CRC, CDX2 is highly suppressed 45 and is inversely correlated with disease progression and metastasis 46 , 47 . However, previous reports suggested that activated CDX2 regulates AXIN2 expression in Caco-2 cells 42 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The complex is formed by ten interdependent interfaces between IL-6 and the two receptors, and between the receptors, with the earlier binding events creating composite binding surfaces to enable subsequent receptor recruitment. The structure of the IL-6 signaling complex has aided drug design studies (139,140), showing its value in the design of novel therapeutics.…”
Section: The Structure Of the Il-6 Signaling Complexmentioning
confidence: 99%
“…Bazedoxifene has been shown to suppress STAT3 activation through IL-6, inhibit tumor growth in a murine model of rhabdomyosarcoma, a soft-tissue sarcoma (267), and inhibit the proliferation of IL-6 dependent cell lines (268). Bazedoxifene has also been shown to block STAT3 activation by IL-11 in human cancer cell lines, and reduce the tumor burden in murine models of gastric cancer (140). Bazedoxifene was also shown to inhibit IL-6 signaling in triple negative breast cancer cell lines (269), and in murine models of the inflammatory cardiovascular disease abdominal aortic aneurysm (270).…”
Section: Inhibitors Of Signaling Through Gp130mentioning
confidence: 99%